Haemoglobin levels and blood requirement in thalassaemia. Issue 2 (February 1982) - Gabutti, V; Piga, A; Nicola, P; Vullo, C; Capra, L; Di Palma, A; Masera, G; Terzoli, S; Mauri, R
Abstract : The relationship between blood requirement and the mean level of maintained haemoglobin was examined in 392 patients with homozygous beta-thalassaemia. Pre- and post-transfusional haemoglobin levels and the amounts of blood transfused were measured during a 1-year period. No significant differences were noted in the blood requirements of patients (splenectomised or not) irrespective of the haemoglobin level. It may be supposed that if the mean haemoglobin level is high the haematopoietic activity is inhibited, and hence the bone marrow mass and total blood volume are reduced. High haemoglobin levels may thus be obtained with no increase in blood intake.